Students’ voices on how drama builds English-speaking confidence in an Indonesian university - Pratolo, Bambang Widi; Dewi, Nuria Punjastala (Universitas Ahmad Dahlan, 2025)
This qualitative case study examines how drama supports English speaking confidence among undergraduate students in an English Education Study Program. Data were obtained from video recorded analyses of three performances by seventeen students and interviews with six purposively selected participants. The analysis followed Braun and Clarke’s thematic procedures. Six themes emerged. Repeated practice strengthened confidence. Role play functioned as an emotional shield that reduced self-consciousness. Students experienced a shift from hesitation to greater fluency. Nonverbal behaviors signaled increased assurance. Peer support helped students regulate emotions during performance. Participants viewed drama as more engaging than conventional instruction. The findings align with Bandura’s self-efficacy theory and Krashen’s affective filter hypothesis. Drama provided mastery experiences, social models, persuasive feedback, and reduced anxiety, which supported language development. The study offers practical direction for curriculum design by recommending scaffolded drama tasks in speaking courses. Teachers are encouraged to use role play and impersonation activities to strengthen confidence. The study contributes contextually by examining a compulsory drama course in a private university, providing evidence of confidence gains that are transferable beyond elective drama contexts.